2021
DOI: 10.1101/2021.05.12.21257114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soft-Attention Improves Skin Cancer Classification Performance

Abstract: In clinical applications, neural networks must focus on and highlight the most important parts of an input image. Soft-Attention mechanism enables a neural network to achieve this goal. This paper investigates the effectiveness of Soft-Attention in deep neural architectures. The central aim of Soft-Attention is to boost the value of important features and suppress the noise-inducing features. We compare the performance of VGG, ResNet, InceptionResNetv2 and DenseNet architectures with and without the Soft-Atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
4
2
Order By: Relevance
“…Although we obtained a lower value of 0.034 for the sensitivity metric than Ding et al who achieved tremendous success, we had a higher value of 0.012 for the AUC metric than the relevant study 34 . For the AUC score, our method obtains 0.923, which is 0.036 lower than the best score 35 . Even though our success metrics are slightly lower than those of the most recent studies, our results appear to be significantly superior to ensemble learning studies and other artificial intelligence methodologies.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Although we obtained a lower value of 0.034 for the sensitivity metric than Ding et al who achieved tremendous success, we had a higher value of 0.012 for the AUC metric than the relevant study 34 . For the AUC score, our method obtains 0.923, which is 0.036 lower than the best score 35 . Even though our success metrics are slightly lower than those of the most recent studies, our results appear to be significantly superior to ensemble learning studies and other artificial intelligence methodologies.…”
Section: Discussioncontrasting
confidence: 69%
“…34 For the AUC score, our method obtains 0.923, which is 0.036 lower than the best score. 35 Even though our success metrics are slightly lower than those of the most recent studies, our results appear to be significantly superior to ensemble learning studies and other artificial intelligence methodologies. Our success rate appears to be more than 10% higher than the support vector classifier and KNN techniques.…”
Section: Discussioncontrasting
confidence: 62%
“…Inception ResNetV2 is a pretrained model on million images of ImageNet dataset. To focus more on the skin lesion area, here attention 45 is applied with the Inception ResNetV2 model. A few portions of the input data are enhanced while others are reduced.…”
Section: Methodsmentioning
confidence: 99%
“…In May 2021, Soumyya Kanti Datta and colleagues [20] proposed a method of applying soft-attention to improve performance in skin lesion classification. They found that in skin lesions images, only a small fraction of the pixels are actually involved, while the rest of the image is usually normal skin along with confounding objects such as hairs and blood vessels.…”
Section: Soft-attention Improves Skin Cancer Classification Performancementioning
confidence: 99%